Global trend of open innovation research: A bibliometric analysis - Ha Thi Thu Le; Quyen Thi Mai Dao; Van-Chien Pham; Duong Thuy Tran (Cogent Business & Management, 2019)
A bibliometric approach was conducted to evaluate the global scientific outputs of open innovation based on literature in Social Science Citation Index (SSCI) database from 2003 to 2017, with the ultimate goal of assisting researchers to fulfil the potentiality of open innovation research and to establish future directions. Overall, 1,046 articles in 318 journals were analysed by research performance of countries, continents and institutes, authorship, journals, most cited articles, first articles, author-keywords, keywords plus and paper titles to identify relevant trends in this period. This study demonstrates that Europe was the most productive continent featured by Italy's remarkable surge by 150% in total articles between 2016 and 2017. However, with respect to research performance by country, the USA came top with the highest total number of articles. The analysis of keywords groups in this study shows that while intangible assets were given decreasing attention, issues pertaining to business performance, firm openness and innovation capacity became foci in open innovation research. Articles were published by top journals which all featured the 'management' field in their subject categories, indicating that open innovation spectrum was mainly explored in the field of management.
Keywords: 650; bibliometric research; open innovation; knowledge; research performance